PERUBAHAN FUNGSI WAKAF MENURUT KOMPILASI HUKUM ISLAM - Mhd Yusuf Said (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2016)
Waqf as one of the charitable cause in the Islamic shariah is very useful for the welfare of society, for example, to the advancement of science and culture as well as other development interests are blessed by Allah SWT. Regarding the waqf property, in principle, which has diwakafkan waqf property can not be changed as stated in the hadith Rasul SAW. that the object should not be in perjualbelikan waqf, assigned or inherited.History Mujahid ulama agreed that the waqf property is not allowed to change it from what it professed the wakif exception in urgency due to the interest of the common goal. State waqf objects can not be used again as the wakif swore. Conditions change waqf objects arranged in KHI in line with what was raised the previous mujtahid Imam. as the sound of KHI Article 225 states are essentially the objects that have diwakafkan can notbe changed or other use and what is meant pledge endowments. Except with the first reason for not complying anymore with the purpose of waqf as professed by wakif, both because of the public interest. Provisions stipulated in article 225 above KHI whose purpose is to give a chance to change things endowments in urgency, in order of importance beneficiaries are greater than ever.Keywords: Fungsi Wakaf, Kompilasi Hukum Islam.